2018
DOI: 10.3390/md16080280
|View full text |Cite
|
Sign up to set email alerts
|

Perylenequione Derivatives with Anticancer Activities Isolated from the Marine Sponge-Derived Fungus, Alternaria sp. SCSIO41014

Abstract: Seven new secondary metabolites classified as two perylenequinone derivatives (1 and 2), an altenusin derivative (3), two phthalide racemates (4 and 5), and two phenol derivatives (6 and 7), along with twenty-one known compounds (8–28) were isolated from cultures of the sponge-derived fungus, Alternaria sp. SCSIO41014. The structures and absolute configurations of these new compounds (1–7) were determined by spectroscopic analysis, X-ray single crystal diffraction, chiral-phase HPLC separation, and comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…The observed HMBC correlations from H-7 to C-5 and from H-6 to C-8 suggested that there is a C-8/C-5 linkage. The above data revealed that compound 1 was structurally similar to altertoxin VII [11], except for the absence of a hydroxyl group located at C-7 . The ECD curve of 1 showed negative Cotton effects (CEs) around 225 and 260 nm and positive one around 280 nm, which is very similar to that of altertoxin VII [11], suggesting their same absolute configuration, i.e., 1 R.…”
Section: Resultsmentioning
confidence: 70%
“…The observed HMBC correlations from H-7 to C-5 and from H-6 to C-8 suggested that there is a C-8/C-5 linkage. The above data revealed that compound 1 was structurally similar to altertoxin VII [11], except for the absence of a hydroxyl group located at C-7 . The ECD curve of 1 showed negative Cotton effects (CEs) around 225 and 260 nm and positive one around 280 nm, which is very similar to that of altertoxin VII [11], suggesting their same absolute configuration, i.e., 1 R.…”
Section: Resultsmentioning
confidence: 70%
“…The observed HMBC correlations from H-7 to C-5' and from H-6' to C-8 suggested that there is a C-8/C-5' linkage. The above data revealed that compound 1 was structurally similar to altertoxin VII [9], except for the absence of a hydroxyl group located at C-7' (δC 126.2). The ECD curve of 1 showed negative Cotton effects (CEs) around 225 and 260 nm and positive one around 280 nm, which is very similar to that of altertoxin VII [9], suggesting their same absolute configuration, i.e.…”
Section: Resultsmentioning
confidence: 77%
“…Amidst the many compounds already reported in this class, some nodes in the cluster were not annotated, and may represent potentially novel compounds. Some other annotated parent ions include the phenolic compound alternariphent A1 [41], alkaloid stachybotrin A [39] and nortriterpenoid helvolic acid methyl ester [65] with reported antibacterial and antifungal activities (DNP). The minimal activities observed against the tested pathogens (Table S3) may be attributed to a low concentration of the bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in the annotation of about 10% of the parent ions ( Figure 6). Some annotated ions included the indole alkaloid cytochalasin R [36], pyranone betulinan C [37], alkaloids, 3-acetyl-5-isopropyl-pyrrolidine-2,4-dione [38] and stachybotrin A [39], phenol derivative alternariphent A1 [40,41] and nortriterpenoid deacetyl helvolic acid [42]. Although two fungal isolates emerged in two different clades in the phylogenetic analysis ( Figure S1) belonging to the orders Capnodiales (Cladosporium sp.)…”
Section: Metabolomicsmentioning
confidence: 99%